PENGARUH MOTIVASI BELAJAR DENGAN MENGGUNAKAN MODEL KUANTUM TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Deby Fauzi Asidiqi (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study was to determine the influence of motivation on learning outcomes of students that using quantum learning model with the direct learning model. The method that used in this research was a quasi experimental with research design nonequivalent control group design. The sampling technique in this research was using cluster random sampling technique. In this research, experiment class using quantum learning model and the control class using direct learning model. The research instrument was given in the form of 10 essay questions. Data analysis techniques to test the hypothesis were using correlation and linearity (simple regression). From the calculation of the hypothesis test obtained correlation r ≤ +1, 0.9032 ≤ +1, thus there is a significant functional relationship between the variables of motivation and learning outcomes of students who using quantum learning model. From the calculation of the linearity hypothesis test (simple regression) obtained Fhitung > Ftabel, 172.68 > 4,09, thus there is a significant functional effect between varaibel motivation and learning outcomes of students who using quantum learning model